Customer-Based Destination Brand Equity Modeling: The Role of Destination Resources, Value for Money, and Value in Use. (January 2018) - Chekalina, Tatiana; Fuchs, Matthias; Lexhagen, Maria
This study contributes to the development of knowledge on transferring the concept of customer-based brand equity to a tourism destination context. Keller's brand equity pyramid is utilized as the comparison framework to reveal similarities, but also overlaps, differences and gaps on both the conceptual and measurement level of existing brand equity models for destinations. Particularly, the inner core of the model depicts the complex mechanisms of how destination resources transform into benefits for tourists overlooked by prior research. This study proposes a customer-based brand equity model for destinations, which consists of five dependent constructs, including awareness, loyalty, and three destination brand promise constructs constituting the inner core of the model, namely, destination resources, value in use, and value for money. The model was repeatedly tested for the leading Swedish mountain destination Åre, by using a linear structural equation modeling approach. Findings confirm the path structure of the proposed model.